Life cycle, survivorship and life expectancy of foliage spider (Marpissa bengalensis) in citrus orchard - Nawab,Muhammad (2018)
ABSTRACT: The post embryonic developmental stages of Marpissa bengalensis (Araneae; Salticidac), the 2nd most abundant predatory species in citrus orchard were collected from the experimental fruit garden, department of Horticulture, located at the campus of University of Agriculture Faisalabad andstudied. Life cycle was observed in the laboratory, which started from egg sac collected from the field along with gravid female and released into the spider cages. The incubation period ranged from 5-15 days. The average eggs hatched were 23.8 eggs/cocoon and hatching % under laboratory conditions was recorded as 73.18%. The average duration of spiderlings span on their mothers back was 7 days. An overall, mean duration of 3rd spiderling stage was of 7.46 days. All spiderlings hatched from 8 cocoons. At the 4th spiderling stage, the average duration was of 10.23 days. In the 5th spiderling stage, the spiderling spent an average of 19.82 days. The 6th and 7th spiderlings stages lasted a total of 23.14 days and 25.86 days respectively. During 8th spiderling stage, the duration was maximum and it was recorded in 28.08 days. On average, from hatching to adult stage, the spiderlings lasted 137 days to attained maturity. Greater mortality was observed in the 3rd and 4th spiderling stages, decreasing thereafter and reaching zero in the 8th spiderling stage.